Optimal utilization of geothermal energy through three organic cycles combined with a thermoelectric generator and an electrolysis unit - Lotfi Ben Said; Ali B.M. Ali; Saman Ahmad Aminian; Kamal Sharma; Aashim Dhawan; Prabhat Sharma; Nidhal Becheikh; Lioua Kolsi (Case Studies in Thermal Engineering)
Over the past several years, numerous studies have been conducted to analyze the feasibility of utilizing various organic cycles to harness geothermal energy as an environmentally friendly and renewable energy source. Nonetheless, there has been a dearth of effort in comparing and deciding on the configuration with higher performance. In order to fulfill this purpose, the exergy-economic performances of three cogeneration systems based on three organic cycles, namely the organic Rankine cycle (ORC), trilateral cycle (TLC), and organic flash cycle (OFC), are compared in the present study. The electricity is produced in the turbines of the ORC and OFC and the expander of the TLC. Hydrogen is another product of the systems, which is produced in a proton exchange membrane electrolyzer. The electrolyzer is fed by the electricity generated by a thermoelectric generator, which is utilized instead of the condenser of the cycles to recuperate the waste heat of the condensation process. The comparison is made among the optimum performances of the three systems employing a three-objective optimization. The TLC configuration brings about the highest exergy efficiency (ηex) equal to 48.43 %. ηex of the ORC and OFC configurations are calculated as 37.48 % and 38.6 %, respectively. A comparison between the ORC and OFC from an overall perspective resulted in the selection of the OFC. Moreover, OFC can be introduced as the configuration that leads to the best economic performance. The specific cost of cogeneration (cco) and total cost rate (C˙tot) in the OFC case are 27.1 % and 23.9 % lower than those of the TLC case, respectively. A comparative examination has demonstrated that the newly proposed systems possess the capability to generate electricity and hydrogen at a substantially lower cost than a previously suggested system.